On Translating Pidgins and Creoles in African Literature - Bandia, Paul (TTR, 1994)
AbstractOn Translating Pidgins and Creoles in African Literature — This paper deals with some of the problems of translating pidgins and creoles in African literature. It begins with an overview of the origins and parallel evolution of the French-based and English-based pidgins spoken in West Africa, throwing light on their status, history, and use in African literature. After a brief sociolinguistic analysis of the two hybrid languages, the paper discusses the difficulty of translating them, by carrying out a thorough analysis of translated examples and suggesting more appropriate solutions where necessary. The paper concludes by highlighting the reasons for the translation difficulties which are not only linguistic but also historical and ideological.